Optimalisasi Layanan Loket Pembayaran Dengan Menggunakan Model Antrian - Jusak Ubjaan; Paulina Wokanubun (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Queue is one of the problems in service that is still a measure of satisfaction. Satisfying service is the hope of the company and consumers. This study aims to determine the optimal amount of service capacity and the length of time required to serve each customer. Data was obtained for 15 days which was done randomly. There are three time conditions that occur in every working day; quiet time (14.00 - 16.00), normal time (10.00 - 12.00), peak time (18.00 - 20.00). The queuing system used is the M/M/S model, with the results of the analysis namely; The level of intensity of service facilities where normal time reaches 0.95, quiet time 0.62, peak time 1.4. The probability of 0 consumers in the system is normal time 0.06, quiet time 0.39, busy time 0.44. The average consumer in the queue for normal times is 16 people, 1 person is quiet and 19 people is busy. The time expected by each consumer is normal time 0.1666 minutes, quiet 0.0238 minutes and busy 0.0204 minutes. The average time consumers spend in queues is normal time 0.1515 minutes, quiet 0.0147 minutes and busy 0.0294 minutes. It is recommended that the management of Hypermart MCM Ambon continue to improve services for consumers.